Analisis Pengaruh Persepsi Profesi, Persepsi Kesejahteraan, dan Lingkungan Keluarga terhadap Minat Menjadi Guru Ekonomi pada Mahasiswa Pendidikan Ekonomi Universitas Sebelas Maret - Raafi Azzis; Feri Setyowibowo (Journal on Education, 2023)
This research aims to determine the influence of professional perceptions, perceived welfare, and family environment on interest in becoming an economics teacher. The sampling technique used probability sampling techniques, namely proportionate random sampling with a sample of 170 UNS Economics Education students. Validity test uses product moment and reliability test uses Cronbach's alpha. The data analysis technique in this research uses descriptive statistical analysis, logistic regression analysis, t test, and F test. The results of this research show that: (1) Perception of the teacher profession has a positive and significant effect on interest in becoming an economics teacher among UNS Economics Education students. (2) Perceptions of teacher welfare do not influence interest in becoming an economics teacher among UNS Economics Education students. (3) The family environment has a positive and significant effect on interest in becoming an economics teacher among UNS Economics Education students. (4) Perceptions of the teacher profession, perceptions of teacher welfare, and family environment simultaneously influence the interest in becoming an economics teacher among UNS Economics Education students.